Diferencial de desempenho entre alunos cotistas e não cotistas nos cursos do Centro de Tecnologia da UFC - Souza Júnior, Francisco José de (2018)
This work investigated the differential in academic performance of students shareholders and non-shareholders students in Mechanical, Civil, Electrical, Chemical, Metallurgical and Mechanical Production Engineering from the Center of Tecnology of Federal University of Ceara, who joined duringin the years 2014 to 2017. Dropout rate, accumulated credits and the Academic Performance Index (IRA in portuguese) of these groups were evaluated through semiannual microdata collected from transcripts of 1.853 students. In addition to the use of descriptive statistical methods, econometric analysis was performed throughout regression for panel with random effects data model, in order to identify the effects of the quota system, controlling some characteristics of the students. In general, the results showed that the groups of shareholders and non-shareholders students, from the surveyed sample, show differences in performance before the entry at the university (different grades), and typically remain different in performance (accumulated credits and IRA) along the course. In five of the six courses analyzed the results showed performance advantages in favor of the students of wide competition, with an approximate fashion effects of 12 credits (one semester) and 1.200 points in Academic Performance Index. With respect to the evasion rate, there was no significant difference between the two groups, with a punctual average greater for the group of quota holders students.